Protection of Rights to The Land of Peoples in Coastal Areas - Heriaksa, Andi Heriaksa; Hijriani, Hijriani (International Journal of Management and Education in Human Development, 2022)
Land ownership and ownership in coastal areas are strictly regulated. Only, the complexity of the coastal matter is not only in relation to the legal certainty of coastal peoples to their region alone, but also the implementation of government policies on the management of the coastal region has not fully advanced in implementing legislation from the central level to the region. As for what's a matter of research is how it grants the protection of rights to the people's land in the coastal region. The purpose of this study is to analyze and evaluate the protection of land rights in coastal areas. Research methods used are normative by use of primary law materials, secondary law materials and non-legal materials. Studies have concluded that the rights of coastal land protection can be given and protected, but at least in accordance with the terms of the national strategic program, the common good, the above-water settlements for indigenous law societies, and/or tourism. Then meet the requirements governed by legislation, the overthrow according to the province/district/city, or the coastal zone plan; Is recommended by the provincial/district/city authorities in terms of unregulated land reduction in the RTRW; Meets the policy of the relevant agencies; As well as the total requirements were exempted from the customary legal community that had been settled down in the coastal region.